Effect evaluation of small claim procedure based on fuzzy comprehensive evaluation. Issue 4 (19th May 2018) - Zou, Yuzhuo; Zhou, Hui
Abstract: In the civil procedure law system, the relevant property cases are divided into small, summary and ordinary procedures. The outcome of the decision-making of the case and the effect of the implementation are affected by large number of subjective factors involved in the small claim litigation process. This paper intends to use the problem-based research strategy as the way to review the operation of the small claim proceedings in Guangzhou, using data mining technology and fuzzy mathematics research method, collects, summarizes and analyzes the key data from the court included in the trial data, the case monitoring indicators and judgment documents, trying to build a small claim litigation impact factor model, and then overall thinking the small claim procedure system.